2012
DOI: 10.1002/nbm.2849
|View full text |Cite
|
Sign up to set email alerts
|

Fraction of unsaturated fatty acids in visceral adipose tissue (VAT) is lower in subjects with high total VAT volume – a combined 1H MRS and volumetric MRI study in male subjects

Abstract: Visceral adipose tissue (VAT) is thought to play an important role in the pathogenesis of obesity and insulin resistance. However, little is known about the composition of VAT with regard to the amount of mono- (MUFAs) and polyunsaturated fatty acids (PUFAs) in triglycerides. Volume-selective MRS was performed in addition to MRI for the quantification of VAT. Analysis comprised proton signals from the vinyl-H group (H-C=C-H), including protons from MUFA+PUFA, and diallylic-H, i.e. methylene-interrupted PUFAs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 22 publications
2
48
0
1
Order By: Relevance
“…The analysis of adipose tissue biopsies in cross-sectional studies found that the size of subcutaneous and visceral adipocytes was negatively associated with dietary PUFA intake, while adipocyte cell number negatively correlated with MUFA and positively correlated with SFA intake [99]. The fatty acid content of visceral fat was also higher in SFA and lower in unsaturated fatty acids compared to subcutaneous fat [97,100], suggesting that the visceral fat depot is a major storage site of SFA. Collectively, epidemiological data appear to support a potential protective role for unsaturated fat against body fat mass accumulation, especially in the abdominal region.…”
Section: Effects Of Unsaturated Fats On Body Weight and Fat Massmentioning
confidence: 95%
“…The analysis of adipose tissue biopsies in cross-sectional studies found that the size of subcutaneous and visceral adipocytes was negatively associated with dietary PUFA intake, while adipocyte cell number negatively correlated with MUFA and positively correlated with SFA intake [99]. The fatty acid content of visceral fat was also higher in SFA and lower in unsaturated fatty acids compared to subcutaneous fat [97,100], suggesting that the visceral fat depot is a major storage site of SFA. Collectively, epidemiological data appear to support a potential protective role for unsaturated fat against body fat mass accumulation, especially in the abdominal region.…”
Section: Effects Of Unsaturated Fats On Body Weight and Fat Massmentioning
confidence: 95%
“…3, 4) and thus can contribute to a risk assessment for the development of obesity-related complications [10,63,64]. In that regard, Machann et al found that the fraction of unsaturated fatty acids in VAT was lower in subjects with high total VAT volume [18]. Thomas et al found the "thin-onthe-outside fat-on-the-inside" subphenotype, with a higher ratio of intraabdominal over subcutaneous abdominal adipose tissue, to have an increased metabolic risk.…”
Section: Obesity Diabetes and Metabolic Syndromementioning
confidence: 99%
“…Selektivna magnetna rezonanca u kombinaciji sa magnetnom rezonancom celog tela može da razdvaja i kvantifikuje volumene grupa adipocita pronađenih u skeletnom mišićnom kompartmanu, kao i količinu triglicerida u i izvan skeletnih mišićnih vlakana [49]. Kvanititativna magnetna rezonanca je dragocen metod za kvantifikovanje malih promena u masnoj masi [50].…”
Section: Pletizmografija Istiskivanjem Vazduha (Bod Pod)unclassified